NLRP3 inflammasome and its inhibitors: a review - Shao, Bo-Zong; Xu, Zhe-Qi; Han, Bin-Ze; Su, Ding-Feng; Liu, Chong (Frontiers in Pharmacology, 2015)
Inflammasomes are newly recognized, vital players in innate immunity. The best characterized is the NLRP3 inflammasome, so-called because the NLRP3 protein in the complex belongs to the family of nucleotide-binding and oligomerization domain-like receptors (NLRs) and is also known as “pyrin domain-containing protein 3”. The NLRP3 inflammasome is associated with onset and progression of various diseases, including metabolic disorders, multiple sclerosis, inflammatory bowel disease, cryopyrin-associated periodic fever syndrome (CAPS), as well as other auto-immune and auto-inflammatory diseases. Several NLRP3 inflammasome inhibitors have been described, some of which show promise in the clinic. The present review will describe the structure and mechanisms of activation of the NLRP3 inflammasome, its association with various auto-immune and auto-inflammatory diseases, and the state of research into NLRP3 inflammasome inhibitors.